Pendekatan Kebijakan Lokal (Local Wisdom): Awig-Awig Dalam Pengelolaan Sumber Daya Pesisir Di Provinsi NTB - Vicky Sanofa; Muhammad Sarjan (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
Coastal resource management in the West Nusa Tenggara (NTB) Province has faced various challenges, ranging from environmental degradation to resource use conflicts. The approach of local policies or local wisdom emerges as a potential solution to address these issues. This study aims to examine how local wisdom can be integrated into coastal resource management policies in NTB. The method used involves observation and literature review. The findings indicate that local wisdom, such as awig-awig in the West Nusa Tenggara Province and interactive communicative strategies in Sumbawa, holds great potential in enhancing ecological intelligence and sustainable coastal resource management.